Temporary uterine artery blocking and uterine artery embolization in treating cesarean scar pregnancy - Kefei Zeng; Xianghua Lei; Tingting Xia (Videosurgery and Other Miniinvasive Techniques)
Introduction: Cesarean scar pregnancy (CSP) is a rare form of ectopic pregnancy. Lack of timely CSP treatment can lead to severe postpartum bleeding, affect fertility, and threaten patients’ life and health.